2003
DOI: 10.1029/2001wr000794
|View full text |Cite
|
Sign up to set email alerts
|

Determining the sources of suspended sediment in a forested catchment in southeastern Australia

Abstract: [1] Knowledge is scarce regarding the relative contributions from harvested areas and unsealed roads to sediments in forested catchments. We investigate the source composition of suspended sediment using sediment tracers and an improved multivariate mixing model. Sediment samples were collected during six rainfall events. Geochemical and radiometric tracer properties were corrected for particle size and organic content as well as conservativeness during erosion and sediment delivery. The mixing model incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(165 citation statements)
references
References 47 publications
1
163
0
1
Order By: Relevance
“…The roads increased erosion rates 750-fold compared to non-harvested areas. Motha et al [33] examined managed Eucalyptus stands in Australia. They found that graveled forest roads and non-graveled decks and skid trails comprised less than 3% of the area, but disproportionately contributed between 6% and 25% of stream sediment.…”
Section: Forest Roads Erosion and Sedimentmentioning
confidence: 99%
“…The roads increased erosion rates 750-fold compared to non-harvested areas. Motha et al [33] examined managed Eucalyptus stands in Australia. They found that graveled forest roads and non-graveled decks and skid trails comprised less than 3% of the area, but disproportionately contributed between 6% and 25% of stream sediment.…”
Section: Forest Roads Erosion and Sedimentmentioning
confidence: 99%
“…Apart from these effects, tree clearing from logged sites can also cause an increase in erosion and subsequently increase the sediment yield (McGurk et al, 1996). Also, harvested areas can contribute up to five times more sediment than undisturbed sites (Motha et al, 2003). In terms of the potential channel responses to increased discharge, the riverine system can experience changes in the width to depth ratio of the channel due to greater undercutting at the banks and the movement of sediment and wood in the streams (Montgomery and Buffington, 1997).…”
Section: Channel Form Analysismentioning
confidence: 99%
“…However, using single property or component signatures is likely to prove unrealistic and result in spurious linkages between source materials and sediment (Collins and Walling 2002), so most fingerprinting studies now employ composite fingerprints, which comprise a range of different diagnostic properties influenced by contrasting environmental controls, and thereby greatly improve the reliability of sediment source discrimination (Walling et al 2006). Today composite fingerprints have been successfully employed by mixing models for source tracing and determining the relative importance of individual sediment source types in a number of different contexts (Walling and Woodward 1995, Russell et al 2001, Motha 2003, Miller et al 2005, Walling et al 2006, Collins and Walling 2007, Minella et al 2008, Collins et al 2010a, 2010b.…”
Section: Introductionmentioning
confidence: 99%